Global Infection Rate of Rotavirus C during 1980–2022 and Analysis of Critical Factors in the Host Range Restriction of Virus VP4 - Simiao Zhao; Xinshun Jin; Lingling Zang; Ziwei Liu; Xiaobo Wen; Xuhua Ran (Viruses, 2022)
Information on rotavirus C (RVC) infection is lacking, partly because the prevalence of RVC among humans and animals worldwide is undefined. Data on the characteristics of the P genotype among RVC strains are also required. We performed systematic searches on the infection rates of RVC since 1980 based on the literature and gene sequences of the PubMed and GenBank databases. A phylogenetic tree of VP4 genes was constructed to evaluate the distribution of the P genotype of RVC from various hosts. The specific mutation motifs in VP8* with P [2]/P [4]/P [5] specificity were analyzed to elucidate their roles in host range restriction. The rate of RVC infection in humans has fallen from 3% before 2009 to 1%, whereas in animals it has risen from 10% to 25%. The P genotype of RVC showed strict host species specificity, and current human RVC infections are exclusively caused by genotype P [2]. In the VP8* hemagglutinin domain of the P [4]/P [5] genotype of swine RVC, specific insertion or deletion were found relative to the human P [2] genotype, and these motifs are a possible critical factor for host range restriction. Our findings highlight the need for further epidemiological surveillance, preventive strategies, and elucidation of the factors involved in the specific host range restriction of RVC-circulating strains.